All-in-One Bacmids: an Efficient Reverse Genetics Strategy for Influenza A Virus Vaccines - Chen, Hongjun (American Society for Microbiology, 2014)
Vaccination is the first line of defense against influenza virus infection, yet influenza vaccine production methods are slow, antiquated, and expensive as a means to effectively reduce the virus burden during epidemic or pandemic periods. There is a great need for alternative influenza vaccines and vaccination methods with a global scale of impact. We demonstrate here a strategy to generate influenza A virus in vivo by using bacmid DNAs. Compared to the classical reverse genetics system, the “eight-in-one” bacmids (bcmd-RGFlu) showed higher efficiency of virus rescue in various cell types. Using a transfection-based inoculation (TBI) system, intranasal delivery to DBA/2J and BALB/c mice of bcmd-RGFlu plus 293T cells led to the generation of lethal PR8 virus in vivo. A prime-boost intranasal vaccination strategy using TBI in the context of a bcmd-RGFlu carrying a temperature-sensitive H1N1 virus resulted in protection of mice against lethal challenge with the PR8 strain. Taken together, these studies provide proof of principle to highlight the potential of vaccination against influenza virus by using in vivo reverse genetics. IMPORTANCE Vaccination is the first line of defense against influenza virus infections. A major drawback in the preparation of influenza vaccines is that production relies on a heavily time-consuming process of growing the viruses in eggs. We propose a radical change in the way influenza vaccination is approached, in which a recombinant bacmid, a shuttle vector that can be propagated in both Escherichia coli and insect cells, carries an influenza virus infectious clone (bcmd-RGFlu). Using a surrogate cell system, we found that intranasal delivery of bcmd-RGFlu resulted in generation of influenza virus in mice. Furthermore, mice vaccinated with this system were protected against lethal influenza virus challenge. The study serves as a proof of principle of a potentially universal vaccine platform against influenza virus and other pathogens.